7(n-12)-52n=62

Simple and best practice solution for 7(n-12)-52n=62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(n-12)-52n=62 equation:


Simplifying
7(n + -12) + -52n = 62

Reorder the terms:
7(-12 + n) + -52n = 62
(-12 * 7 + n * 7) + -52n = 62
(-84 + 7n) + -52n = 62

Combine like terms: 7n + -52n = -45n
-84 + -45n = 62

Solving
-84 + -45n = 62

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '84' to each side of the equation.
-84 + 84 + -45n = 62 + 84

Combine like terms: -84 + 84 = 0
0 + -45n = 62 + 84
-45n = 62 + 84

Combine like terms: 62 + 84 = 146
-45n = 146

Divide each side by '-45'.
n = -3.244444444

Simplifying
n = -3.244444444

See similar equations:

| 3px=2q(r-5x)1 | | -2x-1x=-2 | | (2x^2+5-3)=0 | | g-500=225-g | | -(-10+4)+-(-40)= | | 3x^3+x^2-10=0 | | 3t-1=4t+16 | | .5r-.25=.5-.25r | | 2y^2-6y+8=0 | | 8z=2(4z+2) | | 3-2n=13+3n | | 69c-(27c-51)= | | 4+(d+2)-2d=3(2+d) | | 7a^3+b^4= | | r+10=7t-14 | | -12-(-12)-4+(-6)= | | 19+52y-11+7=62 | | 7m+49+4m=137 | | 2x^3-42x^2+252x-352=0 | | 1360*0.45= | | 90x-9x^2-100=0 | | 0+12=12 | | -(t+1)= | | 15-21=-n | | .45x=62.49 | | 5(12-2e)=20 | | -10-(-9)-5+(-3)= | | 19x+5y=8 | | 11(2x-2)+8=74 | | 6x-54=-12x+36 | | -(x-75)= | | 3(4x+9)=75 |

Equations solver categories